African Human Rights Law Reports 2006 Edited by The African Commssion on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria - Edited by The African Commssion on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2008)
African Human Rights Law Reports 2006 Edited by The African Commssion on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria 2008 ISSN: 1812-2418 Pages: xl 359 Print version: Available Electronic version: Free PDF available